Pengaruh Penggunaan Media Peta Interaktif Digital terhadap Motivasi dan Pemahaman Konsep Geografis ASEAN pada Siswa Sekolah Dasar - Nazwa Kusumawicitra; Salma Irdilah; Yona Wahyuningsih (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2025)
Advances in digital technology provide numerous opportunities to improve the quality of education, particularly in Social Studies (IPS) learning at the elementary school level. One important innovation is the use of digital interactive map media that enables students to learn geography in a visual, engaging, and relevant way. However, in practice, IPS learning in elementary schools is still dominated by conventional methods that rely on static printed maps, resulting in low student motivation and suboptimal understanding of geographic concepts, particularly those related to the ASEAN region. This study aims to evaluate the impact of using digital interactive map media on learning motivation and understanding of ASEAN geographic concepts among elementary school students. This study uses a Systematic Literature Review (SLR) approach following the PRISMA 2020 procedure. The research findings indicate that consistent use of digital interactive map media can improve students' motivation in learning and their understanding of geographic concepts. Interactive visualizations encourage active engagement and enthusiasm, and help students better understand spatial concepts. Therefore, digital interactive maps can be an innovative and effective social studies learning option that aligns with the principles of the Independent Curriculum and the Pancasila Student Profile.